Sistem Pemupukan Otomatis Berdasarkan Unsur Hara Tanah Tanaman Tomat Berbasis Internet of Things (IoT) - Cyntia Widiasari; Tia Febri Ananda (ABEC Indonesia, 2022)
Along with the development of technology, the application of technology in agriculture is veryimportant. Due to the increasing need for plant monitoring and care. Fertilizer watering is usually donemanually, this method is less effective because the selection of fertilizers is not in accordance with soilconditions and farmers often forget the fertilization schedule that should be done on time. Based on previousstudies, the fertilization system designed only works based on scheduling indicators without paying attention toindicators of the soil condition itself. This will result in an unfavorable impact on tomato plants due to errors ingiving the type of fertilizer. Therefore, an automatic plant fertilization system is needed that is equipped with amonitoring system via the internet and pays attention to indicators of the condition of soil nutrients, so that thequality of plants can increase and make the work of farmers easier. This tool consists of a PH sensor thatsupports Android as a PH indicator, a RTC as an instruction for scheduling time, a 12V DC pump for thefertilizer water process, a relay as a connector and performance breaker for the pump, and an ESP8266 MCUNode as a microcontroller programmed to. Run the tool and regulate the fertilizer application process. From thissystem, it is hoped that it will make it easier for farmers to schedule fertilization and at the same time know thePH value of the soil to determine the type of fertilizer needed.